Improving Softskills of College Students in PPBSBJ Course With Adaptation of The Innocamp Method - Endang Nurhayati; Venny Indria Ekowati; Ines Ika Saputri (Jurnal Penelitian Humaniora, 2018)
This study was aimed at improving student softskills in solving problems on the development, training, and preservation of language, literature, and Javanese culture in practice in Mata Kuliah Pembinaan Bahasa, Sastra, dan Budaya Jawa (PPBSBJ) course with the adaptation of the innocamp method. It was categorized as quantitative descriptive study. The instruments used were: (1) questionnaire of pretest and posttest, and (2) observation sheet. The qualitative data in this study were obtained by two methods, namely: literature and field studies with interviews and questionnaires. While quantitative data were gathered in the form of pre-test and post-test. The population of the study was 24 people. The success of the method application was seen if 75% of the total number of students who took part in the learning had scored ≥75. Based on the research, it was proven that the innocamp method is effective for improving softskills. Improvement can also be seen from the difference between before and after logit values. The value after application was higher than before the application of the method. Based on the data analysis, it was also found that the average soft skill value increased when compared to before applying the innocamp method. The original soft skill score was 67.80 and increased up to 81.70.Peningkatan Softskills Mahasiswa dalam Mata Kuliah PPBSBJ dengan Adaptasi Metode Innocamp.Penelitian ini bertujuan untuk meningkatkan softskills mahasiswa dalam penyelesaian permasalahan seputar pengembangan, pembinaan, dan pelestarian bahasa, sastra, dan budaya Jawa secara nyata dalam Mata Kuliah Pembinaan Bahasa, Sastra, dan Budaya Jawa (PPBSBJ) dengan adaptasi metode innocamp. Jenis penelitian ini penelitian deskriptif kuantitatif. Instrumen yang digunakan yaitu: (1) kuesioner pre test dan post test, dan (2) lembar pengamatan. Populasi penelitian 24 orang. Keberhasilan penerapan metode dilihat apabila 75 % dari jumlah mahasiswa yang mengikuti pembelajaran telah mendapat skor ≥ 75. Berdasarkan penelitian terbukti bahwa metode innocamp efektif untuk meningkatkan kemampuan softskills. Berdasarkan pengujian hipotesis, didapatkan hasil nilai sig 0,000 (nilai sig 0,05). Simpulan pengujian hipotesis menolak H0 artinya ada pebedaan sebelum dan sesudah diterapkan metode. Peningkatan juga dapat dilihat dari selisih nilai logit sebelum dan sesudah. Nilai sesudah penerapan lebih tinggi dibandingkan sebelum penerapan metode. Berdasarkan analisis data, juga didapatkan kenaikan rata-rata nilai softskills jika dibandingkan dengan sebelum penerapan metode innocamp. Nilai rata-rata softskills semula yaitu 67,80 dan meningkat menjadi 81,70